Florida Crop/Pest Management Profile: Okra - Mark A. Mossler; Esther Dunn (EDIS, 2005)
Okra can be grown throughout the state, but commercial production is concentrated in the Dade County area and bordering counties. Okra requires warm weather to flourish. Consequently, it is grown throughout the state during the summer, but only in southern Florida during the spring and autumn. Harvest extends from March through November, but most of the production occurs in the summer months (4,6). This document is PI-57, a publication of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date November 2005.